2004
DOI: 10.1359/jbmr.0301226
|View full text |Cite
|
Sign up to set email alerts
|

PTH Differentially Regulates Expression of RANKL and OPG

Abstract: RANKL and OPG gene expressions were measured with and without PTH at different stages of osteoblast development. Mouse stromal cells were cultured in osteoblast differentiating conditions, and RANKL, OPG, COL1, ALP, OC, and PTHRec genes were measured using qRT-PCR. OPG:RANKL ratios indicate that PTH may induce a possible switch in the regulatory mechanism of osteoclastogenesis where OPG is inhibited early and RANKL is increased at late stages of osteoblast differentiation. Introduction: RANKL is essential for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
198
4
18

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(230 citation statements)
references
References 49 publications
(109 reference statements)
10
198
4
18
Order By: Relevance
“…Interestingly, we found that the expression of early differentiation markers for osteoblasts ALP and Col I, was sustained even after 2 weeks in calcifying VSMC (data not shown). Such an expression pattern of ALP and Col I is different from the expression pattern of these genes during osteoblastic differentiation of bone marrow stromal cells (52). Thus, our observations indicate that oxidative stress-induced osteogenic differentiation of VSMC is not simply a mirror image of osteogenic differentiation of osteoblasts.…”
Section: Discussioncontrasting
confidence: 69%
“…Interestingly, we found that the expression of early differentiation markers for osteoblasts ALP and Col I, was sustained even after 2 weeks in calcifying VSMC (data not shown). Such an expression pattern of ALP and Col I is different from the expression pattern of these genes during osteoblastic differentiation of bone marrow stromal cells (52). Thus, our observations indicate that oxidative stress-induced osteogenic differentiation of VSMC is not simply a mirror image of osteogenic differentiation of osteoblasts.…”
Section: Discussioncontrasting
confidence: 69%
“…Calciotropic hormones and cytokines, including PTH, apparently act through a dual mode to inhibit OPG production and stimulate RANKL production (Vega et al 2007). Previous in vitro studies of osteoblasts have indicated that PTH either decreases (Huang et al 2004) or does not affect (Coetzee et al 2007) OPG levels. Decreased OPG gene expression was detected in bone biopsies of patients with primary hyperparathyroidism (PHPT), and was reversed after PTX (Stilgren et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…5-6 pairs of BGsKO mice and control littermates were used for each assay. The primers used for G s ␣ (16), collagen I (17), alkaline phosphatase (18), osteopontin (19), osteocalcin (20), RANKL (21), and osteoprotegrin (18) have been previously published. GAPDH primers were obtained from Applied Biosystems.…”
Section: Methodsmentioning
confidence: 99%